Estimation of Value at Risk (VaR) in the Context of the Global Financial Crisis of 2007-08 : Application on Selected Sectors in India - Chowdhury, Piyali Dutta; Bhattacharya, Basabi (Indian Journal of Research in Capital Markets, 2015)
The most-recent global financial meltdown of 2007-08 has generated concerns among the risk professionals and researchers regarding the effectiveness of alternative risk assessment methodologies. The turbulence caused by the global financial crisis, especially in the stock markets, has greatly challenged risk management. This study undertook empirical estimation of Value-at-Risk, the widely used risk assessment methodology for assessing market risk. The single number, Value-at-Risk, indicates the maximum loss that may be incurred for a given portfolio for a specified time horizon and a confidence level. The study focused on the performance of some major Indian sectors listed on the National Stock Exchange, on which most of the trades are conducted. A hypothetical portfolio, composed with the selected sectoral indices, was also constructed and its performance was examined. The general techniques commonly used to estimate Value-at-Risk are parametric method (Delta Normal method) and non parametric method (Historical Simulation method and Monte Carlo Simulation method). The crucial period addressed in the study refers to the period from 2007-08 and Value-at-Risk was estimated on the selected sectors. The results based on three Value-at-Risk methods were then compared and analyzed. The results revealed that among the estimated Value-at-Risk based on alternative methodologies, Monte Carlo Simulation method yielded the best possible results in all the key elements of Value-at-Risk analysis. Even for the adequately diversified portfolio, the study reflected the way in which the dominant sectors in the market responded to the crisis phase and how they worked upon the hypothetical portfolio.